Case-based accounting learning strategies - Pertiwi, Luh Wahyu Ratna; Ariyanto, Dodik; Suprasto, Herkulanus Bambang; Suartana, I Wayan (International research journal of management, IT and social sciences, 2020)
This study aims to obtain empirical evidence of differences in student learning outcomes. They apply case-based learning with students who do not apply case-based learning. The research method used was an experiment with true experimental design research design, pre-test post-test control group. Two groups were observed, namely the control group and the treatment group. Case-based learning for financial accounting courses is applied to accounting students in the accounting study program at the Faculty of Economics, Warmadewa University semester 2018/2019. The sample was obtained by convenience sampling method. The data analysis technique used was the independent sample t-test. The results showed the case-based learning strategy in financial accounting courses was effective in increasing student’s understanding of the teaching and learning process. The student’s perceptions of case-based learning strategies in financial accounting courses indicate most students perceive case-based learning strategies enhance learning and the level of effective acceptance from classes applying the case method.